The Remaking of the Euro-Mediterranean Vision : Challenging Eurocentrism with Local Perceptions in the Middle East and North Africa. - Görgülü, Aybars. (Global Politics and Security Series, 2019)
The findings and policy recommendations presented in the book aim to contribute to making EU policies more responsive to major challenges in the region, more flexible on the multilateral and the bilateral level and more inclusive of key stakeholders.